2013
DOI: 10.1634/theoncologist.2012-0293
|View full text |Cite
|
Sign up to set email alerts
|

The NOMS Framework: Approach to the Treatment of Spinal Metastatic Tumors

Abstract: Background. Spinal metastases frequently arise in patients with cancer. Modern oncology provides numerous treatment options that include effective systemic, radiation, and surgical options. We delineate and provide the evidence for the neurologic, oncologic, mechanical, and systemic (NOMS) decision framework, which is used at Memorial Sloan-Kettering Cancer Center to determine the optimal therapy for patients with spine metastases. Methods. We provide a literature review of the integral publications that serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
501
1
42

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 654 publications
(548 citation statements)
references
References 48 publications
4
501
1
42
Order By: Relevance
“…13,14 Prostate and liver neoplasms were less frequent; however, there are also many studies reporting the use of SBRT in these sites and feasible protocols available. 15,16 Although our results have shown 25.7% of treatments without a formal protocol statement, a protocol was indeed followed, even though not reported, respecting the dose constraints in healthy surrounding tissue and planning report, in the treatment of all patients. This is in accordance with the institutional policy.…”
Section: Resultsmentioning
confidence: 70%
“…13,14 Prostate and liver neoplasms were less frequent; however, there are also many studies reporting the use of SBRT in these sites and feasible protocols available. 15,16 Although our results have shown 25.7% of treatments without a formal protocol statement, a protocol was indeed followed, even though not reported, respecting the dose constraints in healthy surrounding tissue and planning report, in the treatment of all patients. This is in accordance with the institutional policy.…”
Section: Resultsmentioning
confidence: 70%
“…Since then, various criteria have been developed for the selection of patients that would benefi t most from surgical treatment 9,13 . Th e degree of spinal cord compression has been better defi ned 15 , a framework has been established for considering spinal instability brought about by malignant disease 16 , and most recently, the required extent of treatment has been better defi ned 17 . Th us, spinal surgery has established its place within the complex, multidisciplinary and palliative approach to patients with spinal metastatic disease.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Th e spinal surgeon has an array of treatment options that diff er in invasiveness and how radical the tumor resection should be 17 . Th e most radical operation is en bloc resection of a tumor according to the principles of treatment of primary spinal tumors 12 .…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…44 Laufer et al demonstrated that local progression of spinal metastases was reduced in patients treated with separation surgery followed by high-dose single-fraction (24 Gy) or high-dose hypofractionated SRS (18-36 Gy in 3 fractions) compared with low-dose hypofractionated SRS (18-36 Gy in 5-6 fractions). 43,44 All patients underwent separation surgery with the intent to establish sufficient distance between the residual tumor and the spinal cord, which facilitated the administration of radiosurgery. 43,44 The 1-year recurrence rates were less than 10% in both high-dose cohorts.…”
Section: Separation Surgerymentioning
confidence: 99%